PERAN KETUA KELOMPOK TANI PADA PENINGKATAN PRODUKTIVITAS PADI SAWAH DI DESA MARGOSARI KECAMATAN PAGELARAN UTARA KABUPATEN PRINGSEWU - Mustopa, Mustopa; Rangga, Kordiyana; Aviati, Yuniar (Indonesian Journal of Socio Economics, 2023)
This study aims to determine the roles of the farmer group leader, analyze the relationship between farmer characteristics and the role of the farmer group leader, and determine the relationship between the role of the farmer group chairman and the rice productivity level in Margosari Village, Pagelaran District. North.  This study was determined purposively with the consideration that Margosari Village is a village that has the largest number of farmer group members in North Pagelaran District. The population is all members of farmer groups in Margosari Village with the total of 263 farmers spread across 7 farmer groups with 60 farmers as respondents.  The results showed that the role of the farmer group leaders is included in the moderate classification (76.67%).  There are three characteristics related to the role of the farmer group leaders, namely age, land size, and length of farming experience.  Rice productivity of group members is 5.78 tonnes/ha, this indicates that the productivity level of members of the farmer group in Margosara Village is high enough.